2016
DOI: 10.24036/02016526480-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Konsep Kecemasan (Anxiety) pada Lanjut Usia (Lansia)

Abstract: Lanjut usia merupakan tahap akhir perkembangan pada daur kehidupan manusia yang merupakan suatu proses alami yang tidak dapat dihindari oleh setiap individu. Perubahan-perubahan fisologis maupun psikososial, akan berpotensi pada masalah kesehatan baik fisik maupun psikologis. Salah satu masalah psikologis yang sering terjadi pada lanjut usia pada kondisi kehidupan sosial adalah kecemasan. Kecemasan diartikan suatu kondisi emosi yang menimbulkan ketidaknyamanan ditandai dengan perasan khawatir, kegelisahan dan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
107

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(165 citation statements)
references
References 3 publications
1
57
0
107
Order By: Relevance
“…6 Anxiety is an emotional condition with the emergence of discomfort in a person, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that is not yet clear. 7 The results of this study indicated that the majority of disorders scale in hemodialysis patients after conducting intervention Spiritual Emotional Freedom Technique (SEFT) were 73.3% of 11 respondents, which was in mild anxiety. The related study that has done there found significant differences between levels of depression, anxiety, and stress before and after SEFT intervention (p <0.05), between the intervention group and the control group (p <0.05).…”
Section: Discussionmentioning
confidence: 78%
“…6 Anxiety is an emotional condition with the emergence of discomfort in a person, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that is not yet clear. 7 The results of this study indicated that the majority of disorders scale in hemodialysis patients after conducting intervention Spiritual Emotional Freedom Technique (SEFT) were 73.3% of 11 respondents, which was in mild anxiety. The related study that has done there found significant differences between levels of depression, anxiety, and stress before and after SEFT intervention (p <0.05), between the intervention group and the control group (p <0.05).…”
Section: Discussionmentioning
confidence: 78%
“…Anxiety is a form of neurotic helplessness, insecurity and immaturity feeling, also perpetually overwhelm with the daily life situation [10]. Reinforced by Kartini Kartono's opinion [11] anxiety is a feeling of worry and fear that are strong enough towards an unclear things and situation, as also stated by Sarlito Wirawan Sarwono that anxiety follows from an unknown or poorly defined threat [12].…”
Section: Inmates' Pre-release Social Anxiety Disordermentioning
confidence: 99%
“…Anxiety is a negative emotional state that is characterized by a hunch and somatic tension, such as the heart beating fast, sweating, difficulty breathing. According to Atkinson (in Dona and Ifdil) anxiety is an unpleasant feeling, which is characterized by terms such as worries, concerns, and fears that are sometimes experienced at different levels [4]. From the various meanings of anxiety that have been described above, it can be concluded that anxiety is an emotional condition with a feeling of discomfort in a person, and is a vague experience accompanied by feelings of helplessness and uncertainty caused by something that unclear [4].…”
Section: B Teen Anxiety In Online Mediamentioning
confidence: 99%
“…(3) Realistic anxiety: Realistic anxiety is an unpleasant and non-specific feeling that includes the possibility of the danger itself. Realistic anxiety is the fear of real dangers originating from the outside world [4].…”
Section: B Teen Anxiety In Online Mediamentioning
confidence: 99%